A methodology for design and simulation of soft grippers. (November 2021) - Honarpardaz, Mohammadali
Soft grippers are a growing type of end-effectors that are developed to balance out the simplicity and versatility of the grippers. Today, however, literature lacks a promising method for designing accurate, durable, and high-payload soft grippers. This paper therefore identifies the essential steps in order to design such grippers, and proposes a framework that links the essential steps in order to optimize the design of soft grippers according to the requirements. Finally, functionality and performance of the design grippers are experimentally verified and analyzed via a case study of a real industrial application.